GAYA BAHASA KIASAN DALAM LIRIK LAGU BAND “EFEK RUMAH KACA” ALBUM “EFEK RUMAH KACA, KAMAR GELAP, SINESTESIA”. - Khoirul Anwar, Mohamad; Anwar, M. Shoim (Buana Bastra, 2019)
The art of music is so interested by all humans without exception, from the old, youth,teenagers, until the children itself. With a variety of musical genres, the interesting things in music itself is in the lyrics of songs that contain explicit meanings created by the author toexpress the results of his work to be enjoyed by the public. Each author is able to create his workin various ways, through observation, the stories of others, or even his own personalexperience.The purpose of this study is to describe more deeply and thoroughly about thefigurative style in the lyrics of the band 's "Rumah Efek Kaca" album "Efek Rumah Kaca, KamarGelap, Sinestesia". The theory used in this research is Gorys Keraf style theory. The method usedin this research is qualitative research method. The technique of collecting data is using librarytechnique. The data analysis technique used is descriptive qualitative. The results of the studyfound in the lyrics of the band's band "Rumah Efek Kaca", "Rumah Rumah Kaca, Gelap Room,Sinestesia". There are several kinds of figurative language styles, but there are only two styles oflanguage that more dominant which is the figurative style of language irony and allegorylanguage style. Conclusions and suggestions are given so that this research can be useful for thereaders and the development of learning Indonesian language and literature in studying the styleof language, especially in figurative language style.